GWAS Identifies New Loci for Painful Temporomandibular Disorder: Hispanic Community Health Study/Study of Latinos. (March 2017) - Sanders, A.E.; Jain, D.; Sofer, T.; Kerr, K.F.; Laurie, C.C.; Shaffer, J.R.; Marazita, M.L.; Kaste, L.M.; Slade, G.D.; Fillingim, R.B.; Ohrbach, R.; Maixner, W.; et al.
Temporomandibular disorder (TMD) is a musculoskeletal condition characterized by pain and reduced function in the temporomandibular joint and/or associated masticatory musculature. Prevalence in the United States is 5% and twice as high among women as men. We conducted a discovery genome-wide association study (GWAS) of TMD in 10, 153 participants (769 cases, 9, 384 controls) of the US Hispanic Community Health Study/Study of Latinos (HCHS/SOL). The most promising single-nucleotide polymorphisms (SNPs) were tested in meta-analysis of 4 independent cohorts. One replication cohort was from the United States, and the others were from Germany, Finland, and Brazil, totaling 1, 911 TMD cases and 6, 903 controls. A locus near the sarcoglycan alpha ( SGCA ), rs4794106, was suggestive in the discovery analysis ( P = 2.6 × 10 6 ) and replicated (i.e., 1-tailed P = 0.016) in the Brazilian cohort. In the discovery cohort, sex-stratified analysis identified 2 additional genome-wide significant loci in females. One lying upstream of the relaxin/insulin-like family peptide receptor 2 ( RXP2 ) (chromosome 13, rs60249166, odds ratio [OR] = 0.65, P = 3.6 × 10 −8 ) was replicated among females in the meta-analysis (1-tailed P = 0.052). The other (chromosome 17, rs1531554, OR = 0.68, P = 2.9 × 10 −8 ) was replicated among females (1-tailed P = 0.002), as well as replicated in meta-analysis of both sexes (1-tailed P = 0.021). A novel locus at genome-wide level of significance (rs73460075, OR = 0.56, P = 3.8 × 10 −8 ) in the intron of the dystrophin gene DMD (X chromosome), and a suggestive locus on chromosome 7 (rs73271865, P = 2.9 × 10 −7 ) upstream of the Sp4 Transcription Factor ( SP4 ) gene were identified in the discovery cohort, but neither of these was replicated. The SGCA gene encodes SGCA, which is involved in the cellular structure of muscle fibers and, along with DMD, forms part of the dystrophin-glycoprotein complex. Functional annotation suggested that several of these variants reside in loci that regulate processes relevant to TMD pathobiologic processes.